PENGEMBANGAN EKSTRAKURIKULER KEAGAMAAN DAN UPAYA PENANAMAN AKHLAK DI SEKOLAH - Mohammad Al Farabi; Maja Hamdani (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2022)
Abstract: This study aims to examine and analyze the model of religious extracurricular development and efforts to inculcate morals in schools, where the subject of this research is based on al-Washliyah 80 Kisaran Elementary School. This study uses qualitative methods with data collection techniques using observation, interviews and documentation, while data analysis consisting of data reduction, data presentation, and drawing conclusions. The results of this study are (1) the religious extracurricular development model was developed through three models of developing teaching materials, namely the model of teaching materials based on a science approach; model of teaching materials based on an integrated thematic approach; and a model of teaching materials based on the direction learning approach. The three models of teaching materials are carried out in a measurable and systematic way so that they are able to have a good impact on the cultivation of morality in students at Al-Washliyah 80 Kisaran Elementary School.Keywords: Development Models; Teaching Materials; Religious Extracurriculars